IN-SITU COMPRESSION TEST OF ARTIFICIAL BONE FOAMS IN CONTROLLED ENVIRONMENT USING X-RAY MICRO-COMPUTED TOMOGRAPHY - Jonathan Glinz; Daniel Kytýř; Tomáš Fíla; Jan Šleichrt; Andreas Schrempf; David Fürst; Johann Kastner; Sascha Senck (Acta Polytechnica CTU Proceedings)
In this study, we investigated specimens of artiﬁcial bone foams, developed by the research group for surgical simulators at the UAS Linz, which are used to mimic the haptic feedback of physiologic and pathologic bone for more realistic surgery training. Specimens with two kinds of mineral ﬁller material as well as diﬀerent amounts of foaming agent were tested in an environmental in-situ loading stage developed by the ITAM CAS and scanned via X-ray micro-computed tomography. In this in-situ stage, specimens can be immersed in liquid and tested under temperature-controlled conditions. Consequently, a total amount of 12 specimens was subjected to compression loading; half of them immersed in water at 36.5◦C and half in dry condition. Results showed that there is no signiﬁcant inﬂuence of liquid immersion to the compression outcome. However, foams with less amount of foaming agent appeared to have smaller pores resulting in higher compression strength.